Концепція механізму управління інтелектуальними ресурсами інноваційно активних підприємств (досвід Великої Британії) - Drobyazko, Svetlana; Malakhovskyi, Yurii; Zhovnovach, Ruslana; Mohamed, Mohamed (Dr. Viktor Koval, 2020)
Introduction. Management of competencies of innovative workers in specific conditions of functioning of innovatively active enterprises as producing ecosystems is considered as the dominant direction of managing the process of production of new knowledge, localized within a specific organization, which can increase the consumer value of final consumption goods/services in the process of global value chains’ formation. Aim and tasks. The purpose of the publication is to summarize United Kingdom practices in the management of intellectual resources of innovatively active enterprises. Results. The purpose of the United Kingdom science and innovation policy is to develop the professional skills of the population, to organize world-class research and education, to apply knowledge and skills to develop a competitive economy. The established network of science and innovative policy management entities is in line with the open innovation demand model, which implies the establishment of effective cooperation between universities, business organizations, suppliers, consumers. The generalized model of organizational and economic mechanism of regulation of intellectual resources of innovatively active enterprises personnel as knowledge-intensive sociocentric networks is presented in the form of a structured system focused on the behavioral aspects of the activity of subjects of production of new knowledge of means of regulatory and indicative influence on the configuration of regulatory objects that are subordinated to the sub-system in the conditions of global competition. Conclusions. To fully meet the requirements of innovating the organizational and economic mechanism regulation of intellectual capital’ innovatively active enterprises corresponds to the incorporation into the toolkit of realization of the purpose and tasks of development of the means of forecasting the future state, structure, prospects of increasing the value of its elements. This trend of modernization provides an opportunity to increase intellectual capital through the introduction of Foresight procedures for analysing the impact on it of scientific and technological innovations, formulating and modernizing the mission of forecasting inclusive social capital, comprehensive specification of the regulatory sector, taking into account economic macro and mesoscenarios. At the same time, the proposed means increase the degree of scientific substantiation of the processes of regulation of enterprise development by implementing the analysis of alternative scenarios of intellectual capital growth of innovatively active ecosystems of microeconomic level, open the possibility of developing technological roadmaps for the implementation of targeted programs for long-term research, long-term research development of themes and programs for the implementation of applied social technologies at the request of stakeholders.